PENGEMBANGAN INSTRUMEN TES BERBASIS ANDROID PADA MATERI RUMUS-RUMUS TRIGONOMETERI KELAS X - sundari, elvira; Izzati, Nur (PATTIMURA UNIVERSITY, 2020)
The government expects practicality in using the budget, especially in conducting testing. With the development of technology in the revolutionary era 4.0, the government was able to reduce the budget for conducting tests, namely by using technology. This study aims to develop an android-based test instrument on the appropriate material for trigonometric formulas for class XI SMA. This type of research is Research and Development by applying the Borg and Gall model. This study involved 32 students of class XI MIPA 4 at SMAN 2 Tanjungpinang. The data analysis technique used was content validity and item analysis. The results obtained were 98.9% categorized as very valid by material experts and 100% categorized as very valid by mDevelopmentedia experts and the results of the item analysis showed valid and reliable, the level of difficulty of the test instrument was 68% categorized as moderate, and the distinguishing power of the test instrument was 59% categorized as good.